Picophytoplankton is the main contributor to living carbon and biogenic silica stocks in the oligotrophic Eastern Indian Ocean - Liu, Xiaofang; Zhao, Xiangwei; Sun, Jun; Yue, Shan; Yan, Wenzhuo; Wen, Yujian; Wu, Xi (Frontiers in Marine Science, 2024)
Diatoms (> 2 μm) have traditionally been identified as the primary biological agents linking the carbon (C) and silicon (Si) cycles. However, recent research has shown that picophytoplankton species (< 2 μm) also play a crucial role in the intertwined Si-C biogeochemical cycling in marine ecosystems. In this study, we examined the spatial distribution and vertical variation of micro/nano-diatoms and picophytoplankton in the eastern Indian Ocean (EIO), aimed to differentiate the contributions of living carbon and biogenic silica (bSi) stocks between diatoms and picophytoplankton. The study revealed that the abundance of picophytoplankton surpasses that of diatoms by four to seven orders of magnitude. Synechococcus was predominantly presented in the upper layer, while Prochlorococcus, picoeukaryotes, and diatoms were primarily located in the middle layer. Aggregation Boosted Tree (ABT) and Generalized Additive Models (GAM) analyses revealed that temperature and silicate (DSi) levels strongly influenced the diatom and picophytoplankton communities in the EIO. The fractions smaller than 2 μm made substantial contributions of 86.20%, 55.69%, and 96.86% to chlorophyll a (Chl-a), particulate organic carbon (POC), and living carbon biomass, respectively, underscoring the ecological significance of picophytoplankton in the carbon cycle of oligotrophic regions. Picophytoplankton represented a 33.06% of bSi stocks in the area, comparable to the contribution of diatoms (> 20 μm). Moreover, estimated contributions of diatom living carbon and silicon quota averaged 0.47% and 0.66%, respectively, while that of Synechococcus stood at 2.58% and 1.77%, indicating the predominance of Synechococcus as a weakly siliceous organism with high cell abundance in oligotrophic seas. Overall, this study draws on data from diatom and picophytoplankton biomass in the EIO to offer insights into the disproportionate carbon and silicon budgets in oligotrophic oceans from a biological perspective.